Empirical Evidence on the Evolution of International Earnings - Land, Judy; Lang, Mark H. (The Accounting Review, 2002)
We examine whether cross-country differences in earnings-to-price multiples have changed between 1987–1992 and 1994–1999. Our results suggest that earnings multiples became more similar over this time period for the jurisdictions we analyze, although systematic differences remain. Economic determinants of earnings multiples (e.g., growth rates, interest rates, and returns) do not exhibit similar convergence and do not appear to explain the changes. The convergence is robust to controls for cash flow multiples and is apparent in the valuation of accruals. Accrual/cash flow correlations have also become more similar and generally less negative, suggesting a reduction in earnings smoothing. Overall, our evidence suggests convergence in accounting practice.